Values of Character Education in the Struggle of Sultan Syarif Kasim II in Learning History Through a Scientific Approach in Era 4.0 - Ahmal Ahmal; Nurdiansyah Nurdiansyah; Muhamaad Fendrik (AL-ISHLAH: Jurnal Pendidikan, 2022)
This paper is one of the strategies in history learning to achieve the objectives of history learning which is oriented towards the formation of national character and awareness. Through history learning, identification of the values contained in the struggle of Sultan Syarif Kasim II was carried out during his leadership. History learning by identifying values using a scientific approach based on a digital platform. Learning history in this strategy finds many values contained in the events of the struggle. Before identifying the values, custamized  to the nine values of character education first. Such as 1) love of god and truth; 2) responsible, disciplined and independent; 3) trusted; 4) respect and courtesy; 5) affection, care, and cooperation; 6) confident, creative and never give up; 7) fair and leadership spirit; 8) kind and humble; and 9) tolerant and peace-loving. Referring to those values, it is found in various events of the struggle of Sultan Syarif Kasim II as follows, Sultan always obeys religious lesson, Sultan always helps others, Sultan opposes the Dutch policy of making his people as Rodi workers, Sultan establishes education for women as well, Sultan always keeps peace rather than conflict by moving to the land of Aceh, Sultan leads wisely and wisely, Sultan always respects the court's decisions, and the Sultan sacrifices to surrender his wealth to the Republic of Indonesia for the progress of the nation and state. Based on the findings of those values of character education, the value of the struggle of Sultan Syarif Kasim II can be used as an example for students in the future.